Sense of Resistance for a Cursor Moved by User’s Keystrokes - Kawabe, Takahiro; Ujitoko, Yusuke; Yokosaka, Takumi; Kuroki, Scinob (Frontiers in Psychology, 2021)
Haptic sensation of a material can be modulated by its visual appearance. A technique that utilizes this visual-haptic interaction is called pseudo-haptic feedback. Conventional studies have been investigated pseudo-haptic feedback under the situation wherein a user manipulated a virtual object using a computer mouse, a force-feedback device, and so forth. The present study investigated whether and how it was possible to offer pseudo-haptic feedback to a user who manipulated a virtual object using keystrokes. Participants moved a cursor toward a destination by a key press. While the cursor was moving, the cursor was temporarily slowed down on a square area. The participants' task was to report on a 5-point scale how much resistance they felt to the cursor's movement. In addition to the basic speed of the cursor, the ratio of the basic speed to the speed within the square area was manipulated. In Experiment 1, we found that these two factors interacted significantly with each other, but further analysis showed that the cursor speed within the square area was an important determinant of perceived resistance. In Experiment 2, consistent with the results of the previous experiment, the cursor movement outside of the square area was not required to generate the sense of resistance. Counterintuitively, in Experiment 3, the sense of resistance was caused even without user's keystrokes. We discuss that the sense of resistance for a cursor moved by keystrokes can be triggered visually, but interpreted by the brain as a haptic impression.